Selective Serotonin Reuptake Inhibitors: Antimicrobial Activity Against ESKAPEE Bacteria and Mechanisms of Action - Thiago Hideo Endo; Mariana Homem de Mello Santos; Sara Scandorieiro; Bruna Carolina Gonçalves; Eliana Carolina Vespero; Márcia Regina Eches Perugini; Wander Rogério Pavanelli; Gerson Nakazato; Renata Katsuko Takayama Kobayashi (Antibiotics)
Background: Multidrug-resistant bacteria cause over 700,000 deaths annually, a figure projected to reach 10 million by 2050. Among these bacteria, the ESKAPEE group is notable for its multiple resistance mechanisms. Given the high costs of developing new antimicrobials and the rapid emergence of resistance, drug repositioning offers a promising alternative. Results: This study evaluates the antibacterial activity of sertraline and paroxetine. When tested against clinical and reference strains from the ESKAPEE group, sertraline exhibited minimum inhibitory concentration (MIC) values between 15 and 126 μg/mL, while the MIC values for paroxetine ranged from 60 to 250 μg/mL. Both drugs effectively eradicated bacterial populations within 2 to 24 h and caused morphological changes, such as protrusions and cellular fragmentation, as shown by electron scanning microscopy. Regarding their mechanisms of action as antibacterials, for the first time, increased membrane permeability was detected, as evidenced by heightened dye absorption, along with the increased presence of total proteins and dsDNA in the extracellular medium of Escherichia coli ATCC2 25922 and Staphylococcus aureus ATCC 25923, and oxidative stress was also detected in bacteria treated with sertraline and paroxetine, with reduced efficiency observed in the presence of antioxidants and higher levels of oxygen-reactive species evidenced by their reaction with 6-carboxy-2′,7′-dichlorodihydrofluorescein diacetate. The drugs also inhibited bacterial efflux pumps, increasing ethidium bromide accumulation and enhancing tetracycline activity in resistant strains. Conclusions: These findings indicate that sertraline and paroxetine could serve as alternative treatments against multidrug-resistant bacteria, as well as efflux pump inhibitors (EPIs), and they support further development of antimicrobial agents based on these compounds.